Turkish national cyber-firewall to mitigate countrywide cyber-attacks. (January 2019) - Sari, Arif
Highlights: "Seddulbahir, " the first Turkish national cyber-firewall system is proposed. Artificial neural network radial basis function (RBF-NN) approach is used to generate security rules for 21 different attacks from 66 different network service flows. National Cyber-technologies of developed countries are investigated. Current state of the Turkey Cyber-infrastructure is highlighted. Economic Impact of Volumetric DNS attacks on Turkey between 14th-24th December 2015 are exposed. Required structure of the cyber-technologies to enhance country-wide cyber-security is elaborated. Abstract: This research introduces "Seddulbahir, " the first Turkish national cyber-firewall system. Proposed as the first of its kind, Seddulbahir resists possible cyber-attack threats against Turkey's internet infrastructure. Seddulbahir uses the artificial neural network radial basis function (RBF-NN) approach to generate rules that can detect 21 different attacks classified as probing, DoS (Denial of Service), U2R (User-to-Root), and R2L (Remote-to-Local) through the analysis of 66 different network service flows and based on three communication protocols. Results indicate that our proposed approach detects abnormal traffic with high efficiency, low cost, and has a wide detection range, providing accurate, flexible, and effective results in contrast to traditional methods. This paper also outlines the current state of cyberspace in Turkey, provides an analysis and detailed model of the latest cyber-attacks generated against Turkey, and investigates the working mechanisms of national cyber firewall systems used by developed countries such as Russia, China, and the United States.